The Effectiveness of Promotional Mixes in Influencing Local Consumers to Adopt Green Purchasing Behavior in Petaling District, Malaysia - Chan, Thatcher Mei Ling (2013)
Global environmental issues such as global warming are getting serious since thirty years ago which challenging the ways people live and increase the level of awareness of integrating environmental thoughts into their lifestyle. The new trend of marketing concept is now moving towards to Marketing 3.0 (values-driven era) which marketer is more focus on human spirit by contributing green activities to influence and promote green purchasing behaviors. However, there are some consumers still unaware about these issue especially Malaysian consumers. Research on the effectiveness of promotional mixes in influencing local consumers to adopt green purchasing behaviors is limited. Therefore, this study was conducted to examine which promotion methods have positive influence and which has strongest influence on local consumer’s adoption of green purchasing behaviors and difference between demographic factors and adoption of green purchasing behaviors. A survey method using self-administered questionnaires was carried out to gather data from 390 respondents (family and friends) who have shopping behaviors in Petaling District. The results showed that sales promotion and public relation has positive influence on local consumer’s adoption on green purchasing behaviors. Discussion and recommendations are provided in the last chapter.